Membangun Badan Usaha Milik Pesantren (BUMP) Dalam Upaya Menjaga Stabilitas Keuangan Pondok Modern Al-Jauhar, Riau - Fauzi, Syahrul; Agung Setiabudi (Jurnal Pelita Manajemen Pendidikan, 2024)
The presence of this research aims to examine more deeply the management of Islamic Boarding School Owned Business Entities (BUMP) which are managed by Pondok Modern Al-Jauhar with the term Pondok Modern Business Entities (BUPM). With this research, it is hoped that it will be able to contribute and make a contribution in the development of knowledge, especially knowledge about Islamic education management which focuses on the management of Islamic boarding schools, provides benefits for readers and provides additional references for future researchers with relevant themes. This study used a qualitative descriptive exploratory method with a participant research model, directly examining phenomena in the field in a natural setting. Obtaining data by means of observation, interviews, and documentation. The research subjects were selected according to the 3M criteria (knowing, understanding, experiencing), conducting interviews with the snowball sampling model. Analysis of the data that has been obtained through the stages of transcription, coding, grouping, comparing and contrasting, ensuring the validity and validity of the data is carried out using technical triangulation and source triangulation. The results show that establishing a Pesantren Owned Enterprise (BUMP) is necessary to maintain the financial stability of Islamic boarding schools and not rely solely on the government budget and donations from donors (community). The Pondok Modern Business Entity (BUPM) managed by PM Al-Jauhar Riau was officially established in 2018, but before that this Islamic boarding school had only managed business entities such as canteens and laundry. However, over time it has been able to build business units engaged in the food sector to fashion. The existence of this business unit is very helpful in increasing the economy of Islamic boarding schools which are used for operational development and renovating existing facilities. Hadirnya penelitian ini bertuan untuk mengkaji lebih dalam mengenai pengelolaan Badan Usaha Miliki Pesantren (BUMP) yang dikelola oleh Pondok Modern Al-Jauhar dengan istilah Badan Usaha Pondok Modern (BUPM). Dengan adanya penelitian ini diharapkan mampu berkontribusi serta memberikan sumbangsih dalam pengembangan ilmu pengetahuan khususnya keilmuan tentang manajemen pendidikan islam yang berfokus pada pengelolaan pondok pesantren, memeberikan manfaat bagi pembaca dan memberikan referensi tambahan bagi peneliti selanjutnya dengan tema yang relevan. Penelitian ini menggunakan metode kualitatif deskriptif eksploratif dengan model participant research, menelaah secara langsung fenomena dilapangan secara natural setting. Perolehan data dengan cara observasi, wawancara, serta dokumentasi. Subjek penelitian yang dipilih sesuai dengan kriteria 3M (mengetahui, memahami, mengalami), melakukan wawancara dengan model snowball sampling. Analisis data yang telah diperoleh melalui tahapan transcript, coding, grouping, comparing dan contrasting, memastikan keabsahan dan validitas data dilakukan dengan menggunakan triangulasi teknik dan triangulasi sumber. Hasil menunjukkan bahwasannya membangun Badan Usaha Milik Pesantren (BUMP) perlu adanya untuk menjaga stabilitas keuangan pesantren dan tidak hanya bertumpu pada anggaran pemerintah serta sumbangan para donatur (masyarakat). Badan Usaha Pondok Modern (BUPM) yang dikelola oleh PM Al-Jauhar Riau telah didirikan secara resmi pada tahun 2018 silam, akan tetapi sebelum itu pesantren ini telah mengelola badan usaha seperti kantin dan loundry saja. Namun seiring berjalannya waktu telah mampu membangun unit usaha yang bergerak pada sektor makanan hingga fashion. Dengan adanya unit usaha tersebut sangat membantu meningatkan perekonomian pesantren yang digunakan untuk pembangunan operasional serta merenovasi sarana yang telah ada.